Genome-Wide Identification of VQ Motif-Containing Proteins and their Expression Profiles Under Abiotic Stresses in Maize - Song, Weibin; Zhao, Haiming; Zhang, Xiangbo; Lei, Lei; Lai, Jinsheng (Frontiers in Plant Science, 2016)
VQ motif-containing proteins play crucial roles in abiotic stress responses in plants. Recent studies have shown that some VQ proteins physically interact with WRKY transcription factors to activate downstream genes. In the present study, we identified and characterized genes encoding VQ motif-containing proteins using the most recent version of the maize genome sequence. In total, 61VQ genes were identified. In a cluster analysis, these genes clustered into nine groups together with their homologous genes in rice and Arabidopsis. Most of the VQ genes (57 out of 61 numbers) identified in maize were found to be single-copy genes. Analyses of RNA-seq data obtained using seedlings under long-term drought treatment showed that the expression levels of most ZmVQ genes (41 out of 61 members) changed during the drought stress response. Quantitative real-time PCR analyses showed that most of the ZmVQ genes were responsive to NaCl treatment. Also, approximately half of the ZmVQ genes were co-expressed with ZmWRKY genes. The identification of these VQ genes in the maize genome and knowledge of their expression profiles under drought and osmotic stresses will provide a solid foundation for exploring their specific functions in the abiotic stress responses of maize.